The role of defective clearance of apoptotic cells in systemic autoimmunity - Muñoz Becerra, Luis Enrique; Lauber, Kirsten; Schiller, Martin; Manfredi, Angelo A.; Herrmann, Martin (Nature reviews. Rheumatology, 2010)
The inefficient clearance of dying cells can result in the accumulation of apoptotic cell remnants. This occurrence is considered an intrinsic defect that can cause the permanent presence of cellular debris responsible for the initiation of systemic autoimmunity in diseases such as systemic lupus erythematosus (SLE). If postapoptotic debris accumulates in germinal centers, activates complement and functions as a survival signal for B cells that have become autoreactive by somatic hypermutation, autoimmunity could arise (etiology). The accumulation of postapoptotic remnants and fragments derived from secondary necrotic cells in the presence of autoantibodies against apoptotic cells or adaptor molecules obliges their pathological elimination and maintains autoinflammation. The autoimmunity that occurs in patients with SLE involves complex antigens that contain nucleic acids, which can function as virus mimetics. Complexes of autoantibodies, proteins and nucleic acids are likely to be mistaken by the immune system for opsonized viruses, resulting in the production of type I interferons, a hallmark of SLE (pathogenesis). The pathogenicity of autoantibodies is thought to strongly increase if autoantigens are accessible for immune-complex formation. The immune complex could be considered a binary pyrogen formed from less proinflammatory components. The accessibility of cognate autoantigens, in turn, is likely to be related to impaired or delayed clearance of apoptotic cells.
Gesehen am 12.05.2023